2002
DOI: 10.1186/1472-6963-2-2
|View full text |Cite
|
Sign up to set email alerts
|

Resource use data by patient report or hospital records: Do they agree?

Abstract: Background: Economic evaluations alongside clinical trials are becoming increasingly common. Cost data are often collected through the use of postal questionnaires; however, the accuracy of this method is uncertain. We compared postal questionnaires with hospital records for collecting data on physiotherapy service use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 11 publications
2
15
0
Order By: Relevance
“…Finally, the primary outcome in this study was based on patient self-reported completion of the follow-up visit. Other studies 59,60 have demonstrated high correlation between self-reports and documented health care use, particularly within a short recall period.…”
Section: Discussionmentioning
confidence: 93%
“…Finally, the primary outcome in this study was based on patient self-reported completion of the follow-up visit. Other studies 59,60 have demonstrated high correlation between self-reports and documented health care use, particularly within a short recall period.…”
Section: Discussionmentioning
confidence: 93%
“…Some studies have shown that patient self-reporting underestimates resource use compared with medical records,57 although it is less inaccurate with shorter recall periods 7. Others, however, reported an overestimation of healthcare utilisation on the basis of patient self-reporting8 9 In reporting the timing of clinical events, patients have been shown to underestimate time intervals since last screening tests 10 11. There are, however, few data on the accuracy of self-reported waiting times.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, we were able to achieve purposive sampling of distinct study groups for comparison. Participants were approached in person at the point of care and utilization history was based on participant self-report and confirmed with chart abstraction (Kennedy, Leigh-Brown, Torgerson, Campbell, & Grant, 2002). Information on presenting concern and visit diagnosis was extracted from the health record and categorized according to an obstetric triage acuity scale ranging from 1 (most acute) to 5 (least acute) (Smithson et al, 2013).…”
Section: Methodsmentioning
confidence: 99%